Hadith #170 - Sahih al-Bukhari - Ibn Seereen (Sahih al-Bukhari)
I said to `Abida, “I have some of the hair of the Prophet (ﷺ) which I got from Anas or from his family.” `Abida replied. “No doubt if I had a single hair of that it would have been dearer to me than the whole world and whatever is in it.”
Grade: Sahih

Hadith #473 - Sahih al-Bukhari - Ibn Seereen (Sahih al-Bukhari)
Abu Huraira said, “Allah’s Messenger (ﷺ) led us in one of the two `Isha’ prayers (Abu Huraira named that prayer but I forgot it).” Abu Huraira added, “He prayed two rak`at and then finished the prayer with Taslim. He stood up near a piece of wood Lying across the mosque and leaned on it in such a way as if he was angry. Then he put his right hand over the left and clasped his hands by interlacing his fingers and then put his J right cheek on the back of his left hand. The people who
Grade: Sahih

Hadith #1222 - Sahih al-Bukhari - Ibn Seereen (Sahih al-Bukhari)
Um ‘Atiyya (an Ansari woman who gave the pledge of allegiance to the Prophet (ﷺ) ) came to Basra to visit her son, but she could not find him. She narrated to us, “The Prophet (ﷺ) came to us while we were giving bath to his (dead) daughter, he said: ‘Wash her three times, five times or more, if you think it necessary, with water and Sidr, and last of all put camphor, and when you finish, notify me.’ ” Um ‘Atiyya added, “After finishing, we informed him and he gave us his waist
Grade: Sahih